An Adlerian Reading of Personality Development in Emma Donoghue’s Room - Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shiva Zaheri Birgani; Mehrnaz Khoshgam (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This research aims to analyze the sadness that led to the trauma of the main characters Ma and Jack in the Room novel by Emma Donoghue. This research aims to understand and find out what is being experienced by Ma in the Room novel by Emma Donoghue. This research aims to illustrate the effect of economic situation on individual's thoughts, lives, norms and values, and to show how this writer, has rendered the personality development in his contemporary society. The significance of the study lies in the fact that most of Emma Donoghue`s novel, mostly the earlier ones, have similar themes but the researcher is going to find personality development in his novel namely, In Room by finding Inferiority Complex, Striving for Success or Superiority, freedom of choice, conscious and unconscious for individualization Process, and social interest issues in the light of Adlerian personality development theory. The researcher tries to highlights how the characters struggle in society and consciously or unconsciously they are trying to discover self.  The best advantage point for understanding the behavior of an individual is from the internal frame of reference from the individual him- or herself. The striving for significance is a movement toward fulfillment of the goal to achieve unique identity and to belong. Adler believed that each person strove for self-improvement having an innate desire to become better, to move forward and onward, to become superior. Adler did not feel that striving for perfection and superiority was a striving for superiority or perfection over others, but rather that it was a movement directed at self-improvement and greater competency. Thus, Room as a literary text represents the psychological state of the characters. Symbols and Characters can be analyzed according to psychoanalytic theory of Alfred Adler.